Przypisy tłumacza w polskim przekładzie zbioru esejów Terra incognita Draga Jančara - Woźnicka, Weronika (Przekłady Literatur Słowiańskich, 2017)
Translator’s Footnotes in the Polish Translation of Drago Jančar’s essays Terra incognita The author has analyzed the translator’s footnotes in the Polish translation of Terra Incognita. The footnotes are problematic, because some people consider them a discredit to the translator, while others think them a sign of erudition. There is also a group of people, who say they are a solution to untranslatability, which is a result of the differences between the languages and cultures. They help to deliver the meaning. The author of the article searches and analyses if the translator was consistent while creating footnotes and if the information important provided in the process is essential and helpful for the reader to understand Slovenian culture. In other words, if the footnotes are a solution to the problems with the untranslatability. Keywords: footnotes, paratexts in translation, essays, Drago Jančar, Slovenian literature